I too am a black woman: Terry McMillan and the reimagining of the contemporary black woman in "Getting to Happy" - Fondo, Blossom N. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Identity in the African American context has often meant racial identity. This is explained by the deeply racialized society in which blacks had to live in America and where, by virtue of their racial identity, they were the subjects of gross abuses. As a consequence, race became the main thrust of much of African American literature.
Keywords: identity politics; sexual politics; personal identity; black popular fiction; black womanhood